Toll-like Receptor 4 Signaling Mediates Gastritis and Gastric Cancer - Zhang, Zepeng; Liu, Ju; Wang, Yi; Zhang, Lei; Zhou, Tong; Huang, Yu; Zhu, Tongtong (Current Molecular Medicine, 2025)
The stomach is a crucial digestive organ in the human body, highly susceptible to inflammation or pathogen invasion, which can lead to various gastric diseases, including gastric cancer. Toll-like receptors (TLRs) are the first line of defense against pathogen invasion. TLR4, a member of the TLRs family, recognizes pathogen and danger-related molecular patterns to induce inflammatory responses. Helicobacter pylori (H. pylori) is a significant factor in gastric health, and TLR4 recognizes H. pylori -LPS to trigger an inflammatory response. Downstream TLR4 signaling generates proinflammatory cytokines that initiate inflammation in the gastric mucosa. In addition, TLR4 gene polymorphisms can increase health risks. This study aims to investigate the contribution of TLR4 to the inflammatory response in gastric diseases and the relation between TLR4 and H. pylori, TLR4 gene polymorphisms, and how TLR4 affects gastric diseases’ possible pathways to provide further insight for future prevention and clinical treatment strategies.
Keywords: gastric cancer